2020
DOI: 10.1002/sctm.19-0317
|View full text |Cite
|
Sign up to set email alerts
|

The antifibrotic adipose-derived stromal cell: Grafted fat enriched with CD74+ adipose-derived stromal cells reduces chronic radiation-induced skin fibrosis

Abstract: Fat grafting can reduce radiation-induced fibrosis. Improved outcomes are found when fat grafts are enriched with adipose-derived stromal cells (ASCs), implicating ASCs as key drivers of soft tissue regeneration. We have identified a subpopulation of ASCs positive for CD74 with enhanced antifibrotic effects. Compared to CD74− and unsorted (US) ASCs, CD74+ ASCs have increased expression of hepatocyte growth factor, fibroblast growth factor 2, and transforming growth factor β3 (TGF-β3) and decreased levels of TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 73 publications
0
20
0
Order By: Relevance
“…Human fetal ADSC secretomes accelerated wound healing rate in rats with radiation-induced skin injury by promoting angiogenesis [ 29 ]. ADSCs have been shown to have antioxidant activity and protect cells from oxidative injury [ 30 ], and CD74 + ADSCs have been reported to possess anti-fibrotic activity [ 31 ]. Fibrosis is the main feature of chronic radiation-induced dermatitis, and our results showed that ADSCs reduce acute skin injury and fibrosis, which is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Human fetal ADSC secretomes accelerated wound healing rate in rats with radiation-induced skin injury by promoting angiogenesis [ 29 ]. ADSCs have been shown to have antioxidant activity and protect cells from oxidative injury [ 30 ], and CD74 + ADSCs have been reported to possess anti-fibrotic activity [ 31 ]. Fibrosis is the main feature of chronic radiation-induced dermatitis, and our results showed that ADSCs reduce acute skin injury and fibrosis, which is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Ten random images of stained fat graft sections for every mouse in all treatment groups were imaged at 10× objective lens of a Leica DM5000 B Light microscope (Leica Microsystems). Fat grafts were scored for a set of parameters by four independent blinded investigators (C.L., D.B.A., E.J.F., S.A.) (Borrelli, Patel, Adem, et al., 2020). Scores ranged from 0 to 5, with 0 representing least presence and 5 representing most presence.…”
Section: Methodsmentioning
confidence: 99%
“…Five regions of interest were chosen for each sample and the average was recorded as the value for each mouse in all treatment groups. Image J software was used for quantification of percent positive pixel counts per high power field using standardized thresholds of brightness similar to previously established methodology (Borrelli, Patel, Adem, et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Borrelli et al [ 42 ] identified a subpopulation of ASCs that were positive for CD74. They proved to have enhanced anti-fibrotic abilities both in vitro and in vivo .…”
Section: Ways To Enhance Ascs Therapeutic Performancementioning
confidence: 99%